Analysis of Administrative Prescription Completeness to Improve Patient Safety in Primary Health Centers - Wita Oileri Tikirik; Riska Yayyu (Journal of Current Health Sciences, 2025)
A prescription is a legal document in the form of a written request from a doctor, dentist, or veterinarian to a pharmacist to provide and dispense medication to a patient in accordance with applicable laws and regulations. Prescriptions can be made in printed (paper-based) or electronic form. The completeness of prescription writing, especially from an administrative perspective, is crucial in preventing medication errors, ensuring clear communication between healthcare professionals, and supporting rational medication practices. However, in various primary healthcare facilities, such as community health centers, prescriptions that do not meet the established administrative standards are still found. This has the potential to increase the risk of errors in the process of preparing and administering medication to patients. This study aims to evaluate the completeness of prescription writing from an administrative perspective at the Bambu Community Health Center during August 2024. This study is descriptive quantitative in nature, using purposive sampling based on 1,674 prescriptions received during that period. The research sample was determined using the Slovin formula, resulting in 323 prescriptions. The results showed that 232 prescriptions (72%) were administratively complete, while 91 prescriptions (28%) were incomplete. The elements most often omitted were the doctor's name (only included in 258 prescriptions) and the doctor's initials (304 prescriptions). Other elements showed a fairly high level of completeness, such as the prescription date (309), R/ mark (323), signa or instructions for use (305), drug name (323), and patient data (310). These findings indicate that there are still weaknesses in meeting administrative prescription standards at Puskesmas, which can have an impact on patient safety and treatment effectiveness. Therefore, efforts need to be made to improve the prescription documentation system and increase medical personnel compliance with Indonesian Minister of Health Regulation No. 73 of 2016 concerning Pharmaceutical Service Standards at Puskesmas. Further research is recommended to explore the relationship between incomplete prescriptions and medication errors at the primary care level. Abstrak. Resep merupakan dokumen legal berupa permintaan tertulis dari dokter, dokter gigi, atau dokter hewan kepada apoteker untuk menyediakan dan menyerahkan obat kepada pasien sesuai peraturan perundang-undangan yang berlaku. Resep dapat dibuat dalam bentuk cetak (paper-based) maupun elektronik. Kelengkapan penulisan resep, khususnya dari aspek administratif, sangat krusial dalam mencegah kesalahan pemberian obat, memastikan kejelasan komunikasi antar tenaga kesehatan, dan mendukung praktik penggunaan obat yang rasional. Namun, di berbagai fasilitas pelayanan kesehatan tingkat pertama, seperti puskesmas, masih ditemukan resep yang tidak memenuhi standar administratif yang ditetapkan. Hal ini berpotensi meningkatkan risiko kesalahan dalam proses penyiapan dan pemberian obat kepada pasien. Penelitian ini bertujuan untuk mengevaluasi tingkat kelengkapan penulisan resep dari aspek administratif di Puskesmas Bambu selama bulan Agustus 2024. Penelitian ini bersifat kuantitatif deskriptif dengan metode purposive sampling, berdasarkan 1.674 resep yang masuk pada periode tersebut. Sampel penelitian ditentukan menggunakan rumus Slovin, sehingga diperoleh 323 resep. Hasil penelitian menunjukkan bahwa 232 resep (72%) dinyatakan lengkap secara administratif, sedangkan 91 resep (28%) tidak lengkap. Rincian elemen yang paling sering tidak tercantum adalah nama dokter (hanya tercantum pada 258 resep) dan paraf dokter (304 resep). Elemen lainnya menunjukkan tingkat kelengkapan cukup tinggi, seperti tanggal resep (309), tanda R/ (323), signa atau aturan pakai (305), nama obat (323), dan data pasien (310). Temuan ini mengindikasikan bahwa masih terdapat kelemahan dalam pemenuhan standar administratif resep di Puskesmas, yang dapat berdampak pada keselamatan pasien dan efektivitas terapi. Oleh karena itu, perlu dilakukan upaya perbaikan sistem dokumentasi resep dan peningkatan kepatuhan tenaga medis terhadap Permenkes RI No. 73 Tahun 2016 tentang Standar Pelayanan Kefarmasian di Puskesmas. Penelitian selanjutnya disarankan untuk menggali lebih dalam hubungan antara ketidaklengkapan resep dengan kejadian medication error di tingkat pelayanan primer